Sulforaphane ameliorates serum starvation-induced muscle atrophy via activation of the Nrf2 pathway in cultured C2C12 cells - Moon, Jae Yun; Kim, Da Jeong; Kim, Hye Sun (Cell Biology International, 2020)
Oxidative stress, an imbalance of redox homeostasis, contributes to the pathogenesis and progress of muscle atrophy. However, it is debated whether oxidative stress is a cause or consequence of muscle atrophy. In this study, we investigated the relationship between menadione-induced oxidative stress and serum starvation-induced muscle atrophy in C2C12 myotubes. We found that atrophic phenotypes including myotube diameter decrease, protein ubiquitination, and the expression of atrogenes were detected under oxidative stress as well as during serum starvation. Oxidative stress during serum starvation was assessed to confirm the correlation. Both intracellular reactive oxygen species (ROS) and protein oxidation were increased in atrophic myotubes. These results indicate that menadione-induced oxidative stress triggers muscle atrophy and vice versa. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a key regulator of cellular response to oxidative stress and it is considered to have a cytoprotective role in the mitigation of muscle atrophy. Transcription of heme oxygenase-1 (HO-1) and NAD(P)H quinone dehydrogenase-1, target genes of Nrf2, was decreased during serum starvation, which is related to decreased nuclear translocation of Nrf2. Pre-treatment of sulforaphane (SFN), a known Nrf2 inducer, before serum starvation showed a protective effect via Nrf2/HO-1 upregulation. SFN can liberate Nrf2 from Keap1, enabling the nuclear translocation of Nrf2. Consequently, the expression of HO-1 increased and intracellular ROS was significantly reduced by SFN pre-treatment. These results demonstrate that oxidative stress mediates the pathophysiology of muscle atrophy, which can be improved via upregulation of the Nrf2-mediated antioxidant response.
Keywords: Animals; Antioxidants; Apoptosis; Cell Line; Cell Survival; Heme Oxygenase-1; Isothiocyanates; Kelch-Like ECH-Associated Protein 1; Membrane Proteins; Mice; Muscle Fibers, Skeletal; Muscular Atrophy; NF-E2-Related Factor 2; Oxidative Stress; Reactive Oxygen Species; Signal Transduction; Sulfoxides; Vitamin K 3; C2C12; HO-1; muscle atrophy; Nrf2; oxidative stress; sulforaphane